Efficacy and safety of corticosteroids in immunocompetent patients with septic shock - Lu, Xin (World J Emerg Med, 2021)
BACKGROUND: The use of corticosteroids in septic shock has been studied for many decades but yielded conflicting results. We conducted a systematic review to evaluate the efficacy and the safety of corticosteroids in immunocompetent patients with septic shock. METHODS: Medline via PubMed, Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, and EMBASE were searched from inception to March 2020. Two reviewers independently identified randomized controlled trials (RCTs) comparing corticosteroids with a control group for immunocompetent patients with septic shock. Data were abstracted and reported following the Cochrane Handbook for Systematic Review of Intervention and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The efficacy outcome included mortality and shock reversal. The safety outcomes were infection, gastrointestinal bleeding, and hyperglycemia. RESULTS: Nine RCTs with a total of 1,298 patients were included. Compared with the control group, corticosteroid group did not lower the short-term (28 or 30 days) mortality (risk ratio [RR] 0.95, 95% confidence interval (CI) 0.85 to 1.06, inconsistency [I(2)]=0%, trial sequential analysis [TSA]-adjusted CI 0.83 to 1.09, moderate-certainty evidence). Corticosteroids significantly shortened the time to shock reversal compared with the control group (mean difference [MD] –21.56 hours; 95% CI –32.95 to –10.16, I(2)=0%; TSA-adjusted CI –33.33 to –9.78, moderate-certainty evidence). The corticosteroid treatment was associated with an increased risk of hyperglycemia but not the infection or gastrointestinal bleeding. CONCLUSIONS: The corticosteroid treatment is not associated with lower short- or long- term mortality compared with placebo in immunocompetent patients with septic shock. However, corticosteroids significantly shorten the time to shock reversal without increasing the risk of infection. The patient’s immune status should also be considered during clinical treatment and clinical trials in future.